2015
DOI: 10.1371/journal.pone.0139680
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for Measles, Mumps, and Rubella (MMR) Immunization in Mesoamerica: Potential Impact on Coverage and Days at Risk

Abstract: BackgroundRecent outbreaks of measles in the Americas have received news and popular attention, noting the importance of vaccination to population health. To estimate the potential increase in immunization coverage and reduction in days at risk if every opportunity to vaccinate a child was used, we analyzed vaccination histories of children 11–59 months of age from large household surveys in Mesoamerica.MethodsOur study included 22,234 children aged less than 59 months in El Salvador, Guatemala, Honduras, Mexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
0
16
0
3
Order By: Relevance
“…It was consistent with the previous reports from home and abroad and it suggested that the higher education level dose not necessarily correlate with the positive health behaviour related to immunization. [17][18][19][20][21] The possible explanations included: first, parents with higher education background were more likely to have a career and they might have less time to spare for their child's immunization. Second, parent with a higher education level might had an increased concern on the quality and safety as important measures for vaccines, leading to a lower rate or an untimely of vaccination uptake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was consistent with the previous reports from home and abroad and it suggested that the higher education level dose not necessarily correlate with the positive health behaviour related to immunization. [17][18][19][20][21] The possible explanations included: first, parents with higher education background were more likely to have a career and they might have less time to spare for their child's immunization. Second, parent with a higher education level might had an increased concern on the quality and safety as important measures for vaccines, leading to a lower rate or an untimely of vaccination uptake.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 22.1% of the participants stated that they had delayed their children's immunization for reasons other than illness or allergy, which was higher than previous studies. Gust 22 found 13% of the surveyed parents had delayed a vaccination for their child in a 2003-2004 national survey and Mokdad 20 found 14% of the surveyed parents had delayed childhood immunizations for reasons other than their child being ill. Additionally, 24.9% of the surveyed parents would refuse to have their children vaccinated with all the recommended vaccinations. It was higher than the results Freed 1 and Gust 22 found, which were only 12% and 6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the limitations of medical resources and economic conditions in different regions, the coverage of vaccination is low, especially in the underdeveloped province of Guangxi. An effective antibody barrier did not form in the crowd and susceptible populations continued to accumulate, thereby leading to a cyclical outbreak of mumps [ 29 ]. MMR was included in the EPI by the Chinese government in 2008.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that effective coverage of vaccines is often lower than the reported crude coverage due to problems with health information systems and cold chains in Africa and other parts of the world. 36 Additionally, the Central African Republic and Congo are among the top ten high-burden countries for tuberculosis based on severity of disease burden (incidence per capita). 37 Conventionally, and like everywhere in Africa, planning for health in francophone Africa has been focused on communicable diseases.…”
Section: Discussionmentioning
confidence: 99%